2019
DOI: 10.1016/j.resuscitation.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic differences in incidence, bystander cardiopulmonary resuscitation and survival from out-of-hospital cardiac arrest: A systematic review

Abstract: Background: Individuals with a low socioeconomic status (SES) may have a greater mortality rate from out of hospital cardiac arrest (OHCA) than those with a high SES. We explored whether SES disparities in OHCA mortality manifest in the incidence of OHCA, the chance of receiving bystander cardiopulmonary resuscitation (CPR) or in the chance of surviving an OHCA. We also studied whether sex and age differences exist in such SES disparities. Methods:The Medline, Embase and Scopus databases were searched from 01-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 76 publications
5
85
1
1
Order By: Relevance
“…Several studies have investigated socioeconomic status (SES) impact on various aspects of OHCA. 3,4,14,15 These have in general focused on prehospital factors like bystander CPR and on outcome. The finding that low SES is associated with worse outcomes have been explained by e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have investigated socioeconomic status (SES) impact on various aspects of OHCA. 3,4,14,15 These have in general focused on prehospital factors like bystander CPR and on outcome. The finding that low SES is associated with worse outcomes have been explained by e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (as well as ours) have reported a lower rate of bystander CPR and discussed about poorer CPR quality in areas with low SES. 4 It is thus likely that a higher proportion of patients with low SES with cardiac cause and shockable ECG rhythm immediately after the arrest, has a non-shockable ECG rhythm upon arrival of prehospital personnel. These patients might be mistaken as having a low risk of a coronary artery cause for the cardiac arrest due to the false assumption that initial ECG rhythm was non-shockable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OHCAs occurring in different areas might impact the EMS response time, and might re ect different socioeconomic status of the countries [3,10]. Shorter response time, younger age, OHCA occurring during the daytime, urban areas, and socioeconomic status are usually associated with better prognosis [15,16,24,25]. However, people who have OHCAs in public locations tend to be healthier, are able to move freely, and probably have less comorbidity, and thus have better outcomes [26].…”
Section: Discussionmentioning
confidence: 99%
“… 13 In a recent review, these results were corroborated, and it was concluded that low SES areas generally showed a higher incidence of OHCA. 14 It is important to further identify factors that lead to a high incidence of OHCA in order to be able to guide health interventions such as placement of public automated external defibrillators (AEDs) and to improve cardiopulmonary resuscitation (CPR) skills in those high-risk areas.…”
Section: Introductionmentioning
confidence: 99%